Peru : 2017 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights Peru's average growth of more than 5.25 percent since 2000, which has led to significantly reduced unemployment and poverty. Inflation is in low single digits, the fiscal position has strengthened, and dollarization has declined markedly. Growth is expected to remain high relative to the region. In particular, GDP growth is projected to slow to about 2.7 percent in 2017, before bouncing back to over 3.75 percent in 2018, as reconstruction spending filters through the economy and projects delayed owing to the Odebrecht scandal start to catch up. Inflation should gradually return to the target range as weather-related factors abate and food price inflation declines.